2022
DOI: 10.1002/hec.4590
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and non‐communicable diseases: Evidence from Indonesia's primary health care system

Abstract: Für den Inhalt der Passauer Diskussionspapiere ist der jeweilige Autor verantwortlich. Es wird gebeten, sich mit Anregungen und Kritik direkt an den Autor zu wenden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 97 publications
0
6
0
2
Order By: Relevance
“…This is a wake-up call about the risks that heat poses to urban communities. 11 Indirectly, climate change and heat can exacerbate all causes and morbidity of certain diseases through reduced physical health. Heat will lead to heat stress and death in the most severe cases.…”
Section: Introductionmentioning
confidence: 99%
“…This is a wake-up call about the risks that heat poses to urban communities. 11 Indirectly, climate change and heat can exacerbate all causes and morbidity of certain diseases through reduced physical health. Heat will lead to heat stress and death in the most severe cases.…”
Section: Introductionmentioning
confidence: 99%
“…The initial point of contact for primary healthcare can be a Puskesmas (public health center), a Klinik Pratama (primary clinic), or a general practitioner. 15 BPJS Health provides sample data for research purposes that contains information on membership and healthcare services. This data records the utilization of BPJS Health services by its members at healthcare facilities that cooperate with BPJS Health and have submitted claims to BPJS Health.…”
Section: Introductionmentioning
confidence: 99%
“…14 The sample data provided by BPJS Health has been used for various research purposes, such as analyzing patterns of chronic disease multimorbidity, 16 evaluating the dengue surveillance system, 17 and investigating the relationship between temperature and primary healthcare visits. 15 A previous study using BPJS Health data linked with daily-district meteorological data investigated the relationship between temperature and primary healthcare visits. The study found that on hot days, all-cause visits increased by 8%, visits with a diabetes diagnosis increased by 25%, and visits with a cardiovascular disease diagnosis increased by 14%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…‡ This chapter is based onFritz (2022). The article benefited greatly from the valuable advice provided by Michael Grimm.…”
mentioning
confidence: 99%